RE-THINKING EXPERIENTIAL LEARNING IN THE DIGITAL AGE: MAKING LEARNING MORE ADAPTIVE AND INTERACTIVE BY VIRTUALLY EXPERIENCING THE BUILT ENVIRONMENT - Madiha Zaman; Fatima Javeed; Qurat-Ul-Ain Asghar (Spectrum of Engineering Sciences, 2025)
This study explores the transformative potentials of experiential learning within the contemporary digital era, emphasizing the significant roles of adaptability and interactivity enabled by virtual interactions with the built environment. Traditional teaching methodologies have been significantly affected by the introduction of digital technologies. This technological intervention is offering an innovative pedagogical framework that is reshaping the learning dynamics and offering a holistic experience that changes the way knowledge is created, delivered, and experienced as a whole. This research is experimenting with a human-centered design approach that critically evaluates the learning experiences using interactive and immersive technologies in an educational scenario. By closely examining the learner interaction, the study reveals how a tailored design solution can effectively enhance the adaptability of the learner and their educational outcomes. The conclusions offer significant understandings of optimizing educational practices with innovative technologies that ensure accessibility, adaptability,and effectiveness in dynamically changing educational settings.